2022
DOI: 10.1038/s41598-021-04171-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of hydrogen peroxide in an intra-meander hyporheic zone at East River, Colorado

Abstract: The traditionally held assumption that photo-dependent processes are the predominant source of H2O2 in natural waters has been recently questioned by an increrasing body of evidence showing the ubiquitiousness of H2O2 in dark water bodies and in groundwater. In this study, we conducted field measurement of H2O2 in an intra-meander hyporheic zone and in surface water at East River, CO. On-site detection using a sensitive chemiluminescence method suggests H2O2 concentrations in groundwater ranging from 6 nM (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(113 reference statements)
1
2
0
Order By: Relevance
“…In Arctic surface waters, Fenton chemistry is calculated to produce CO 2 at rates similar to microbial oxidation (Page et al, 2013). Moreover, Yuan et al (2022) found 6-80 nM H 2 O 2 in a more reducing nearby East River meander and cutoff oxbow sediments, confirming the likelihood of H 2 O 2 being consistently available at our field site. Floodplains experience dynamic oxygen and Fe(II) supply to high-carbon surface soils, making them prime locations for Fenton-mediated SOC oxidation.…”
Section: The Case For Fe(ii)-mediated Oxidationsupporting
confidence: 73%
See 1 more Smart Citation
“…In Arctic surface waters, Fenton chemistry is calculated to produce CO 2 at rates similar to microbial oxidation (Page et al, 2013). Moreover, Yuan et al (2022) found 6-80 nM H 2 O 2 in a more reducing nearby East River meander and cutoff oxbow sediments, confirming the likelihood of H 2 O 2 being consistently available at our field site. Floodplains experience dynamic oxygen and Fe(II) supply to high-carbon surface soils, making them prime locations for Fenton-mediated SOC oxidation.…”
Section: The Case For Fe(ii)-mediated Oxidationsupporting
confidence: 73%
“…It is not likely coincidence that abiotic Fe(II)-mediated organic carbon oxidation has been observed in environments experiencing frequent water saturation -e.g. rain forests, floodplains, and bogs and fenswith active Fe(II)/Fe(III) redox cycling (Inubushi et al, 1984;Liptzin and Silver, 2009;Dubinsky et al, 2010;Lipson et al, 2010) and often significant H 2 O 2 production (Hall and Silver, 2013;Yuan et al, 2022). Floodplains encompass a range of redox conditions over space and time from relatively oxic in meander surface soils to periodically reducing in subsurface soils, and completely reducing in river and cutoff channels.…”
Section: Introductionmentioning
confidence: 99%
“…Dark formation of reactive oxygen species (ROS) including superoxide (O 2 •– ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (•OH) has been increasingly recognized at oxic–anoxic interfaces in subsurface environments. Particularly, •OH (standard reduction potential: 2.8 V) is the most powerful ROS in natural systems which plays an important role in biogeochemical element cycles, such as greenhouse gas emission (e.g., CO 2 and CH 4 ) ,, and natural attenuation of contaminants. , Generally, ferrous iron (Fe­(II)) and reduced natural organic matter (NOM) are considered to be the main contributors to O 2 reduction and •OH formation in the subsurface. , Many studies have reported •OH production from oxygenation of different Fe­(II) species, including dissolved Fe­(II), ligand-complexed Fe­(II), adsorbed Fe­(II), ,, and mineral structure Fe­(II) (e.g., Fe-bearing clay minerals, ,, mackinawite, pyrite, , and siderite).…”
Section: Introductionmentioning
confidence: 99%